REPRESENTASI PERILAKU MANIPULATIF TOKOH GEMA PADA FILM TINGGAL MENINGGAL (2025) - Nur Azizah Febriani Nur Azizah Febriani; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Film Tinggal Meninggal (2025), directed by Kristo Immanuel, reached the top position on Netflix Indonesia in January 2026, centering on Gema, a corporate employee who develops manipulative behaviors after experiencing systematic social neglect. This study aims to analyze how Gema's manipulative behavior is represented through denotation, connotation, and myth in Roland Barthes' semiotics. Using a qualitative descriptive approach with a critical paradigm, this research applies Stuart Hall's representation theory, Gramsci's hegemony, and Cultural Studies, with data drawn from 15 purposively selected scene lexias analyzed through Barthes' five reading codes. Findings reveal that at the denotation level, Gema's manipulation is captured through her fabrication of identity